Pengembangan E-Modul Dengan Model Discovery Learning Berbantuan Fliphtml5 Materi Fungsi dan Unsur Warna CMYK dan RGB Untuk Kelas X Multimedia - Mahfuddin, Trio; Sesunan, Feriansyah; Sagala, Margaretha Karolina; Firdaus, Rangga (Universitas Lampung, 2022)
The development of this electronic module applies a discovery learning model using the fliphtml5 website as a media. This research aims to; 1) Describe the validity of the e-Module with the fliphtml5 assisted discovery learning model, the material of functions and color elements of CMYK and RGB class X Multimedia; 2) Describe the practicality of the e-Modul with a fliphtml5-assisted discovery learning model, material functions and color elements of CMYK and RGB class X Multimedia. This research uses research and development (Research and Development) with a Four-D (4D) development model which includes define, design, develop, and disseminate stages. The subjects in this study were students of class X majoring in Multimedia at SMK Negeri 3 Metro. To find out the response of teachers and students to the e-Module functions and color elements of CMYK and RGB were obtained using the questionnaire method. The research results obtained include; 1) e-Module with discovery learning model on function and color elements of CMYK and RGB has met the validity criteria, namely the average value obtained from the material validity test, media validity test, and practitioner validity test of 89.79% with a very qualitative statement. good; 2) The results of the practicality test of e-Modules with the discovery learning model on the function and color elements of CMYK and RGB obtained an average value of 87.4% with a very good qualitative statement. Key Word :: e-Modul, Discovery Learning, FLIPHTML5